Controlled trial of an mHealth intervention to promote healthy behaviours in adolescence (TeenPower): Effectiveness analysis - Miguel Lopes de Sousa, Pedro (2020)
Aim To evaluate the effectiveness on lifestyle change of an mHealth intervention to promote healthy behaviours in adolescence (TeenPower) and to analyse the predictors of the mHealth intervention effectiveness. Design This study is designed as a non‐randomized controlled trial with a two‐arm structure. Methods Adolescents of 12–16‐year old were recruited from three school districts, with access to the Internet and smartphone/tablet devices. The intervention group was invited to engage in the mHealth intervention (TeenPower) for 6 months in addition to a school‐based intervention. The control group only followed the school‐based intervention. A repeated measures factorial ANOVA was used and the main effectiveness outcome was the lifestyle change measured by the adolescent lifestyle profile. Results The outcomes of the mHealth intervention (TeenPower) show a significant effect on nutrition (ƞ2p = 0.03, p = .03), positive life perspective (ƞ2p = 0.04, p = .01), and global lifestyle (ƞ2p = 0.02, p = .05), with a dropout rate of 62.1%. The analysis of the effectiveness predictors of the mHealth intervention suggested that older adolescents tended to show a significant increase in the rates of stress management (r = .40; p < .05). Conclusions Although the considerable dropout rate, the mHealth intervention presented significant impact on multiple lifestyle domains, providing support for the effectiveness of mHealth interventions for health promotion as an add‐on to standard interdisciplinary interventions. Impact Adolescents must have the necessary and appropriate knowledge for the correct and responsible decision‐making regarding their health and lifestyle. Innovative strategies (mHealth intervention) were used to promote healthy behaviours. This study evaluates the effectiveness of an mHealth intervention (TeenPower) specifically designed for adolescents. We found a significant impact in several lifestyle domains such as health responsibility, nutrition, positive life perspective, and global lifestyle.